Postharvest Handling Of Sweet Potatoes In Sauce Processing CV. Sumber Sari Limbangan Kulon – Brebes - Inka Condro Istia; Wadli Wadli; Yunika Purwanti (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2021)
Sweet potato is a potential carbohydrate producer (as an energy source) and can be used as an alternative food source. One of the varieties of sweet potato, namely yellow sweet potato which contains beta carotene, functions as an antioxidant and helps overcome cancer-causing chemicals that can damage eye tissue. The use of sweet potatoes is still limited, to increase the utility and added value requires innovation, namely by adding to the making of sauce. In the sauce production process at CV. Sumber Sari uses yellow sweet potatoes. Sauce as a thick liquid made from tomato or chili paste which can give a special aroma and taste to a food. The addition of other ingredients such as sugar, salt and food additives. The research objective was to study yellow sweet potato as an additional ingredient in making sauces. This research is expected to provide alternative uses for sweet potatoes, increase the effectiveness and added value of sweet potatoes. Processing of sauces with the addition of sweet potatoes to increase utility and added value was carried out by CV. Sumber Sari. The production process begins with cleaning of raw materials and packaging, material preparation, mixing, processing and packaging. CV Sumber Sari sauce is distributed to agents throughout Central Java